MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN BAHASA INDONESIA MATERI TEKS BERITA MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING DI SMP NEGERI 19 KOTA BOGOR - Irawaty Syamsudin (Universitas Pakuan, 2022)
IMPROVING STUDENT LEARNING OUTCOMES IN INDONESIAN LANGUAGE SUBJECTS ON NEWS TEXTS THROUGH PROBLEM BASED LEARNING MODELS IN JUNIOR HIGH SCHOOLSThe purpose of this study was to determine the increase in student learning outcomes about news text material in Indonesian language subjects in class VIII.B of State Junior High Schools through the use of Problem Based Learning Models. The method used is a classroom action research method which consists of two cycles. Each cycle consists of four stages of research, namely planning, implementing actions, observing, and reflecting. The research data were analyzed using comparative descriptive followed by reflection. Comparative descriptive is done by comparing the initial condition data, cycle 1 and cycle 2, both for learning outcomes. The results of this study indicate that: First, the use of Problem Based Learning Learning Model can improve student learning outcomes about news text material in Indonesian subjects. It is proven that the percentage of student learning outcomes has increased from the initial condition the average daily test score of 69.39 in the first cycle to 74.24 and in the second cycle to 81.06, or in the final condition it increased by 16.8% from the second cycle. beginning. It is proven that the percentage of students' learning mastery increased from the initial condition of 39.39% in the first cycle to 78.79% in the second cycle or in the final condition, it increased by 100% from the initial condition.